2013
DOI: 10.1260/1756-8293.5.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Linear Aerodynamic Model Identification of a Flapping Wing MAV Based on Flight Test Data

Abstract: This paper presents an approach to the system identification of the Delfly II Flapping Wing Micro Air Vehicle (FWMAV) using flight test data. It aims at providing simple FWMAV aerodynamic models that can be used in simulations as well as in nonlinear flight control systems. The undertaken methodology builds on normal aircraft system identification methods and extends these with techniques that are specific to FWMAV model identification. The entire aircraft model identification cycle is discussed covering the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…10. The states in Table 4 that were reconstructed from the position and attitude of the ornithopter can be found in [21].…”
Section: A Force and Moment Identification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10. The states in Table 4 that were reconstructed from the position and attitude of the ornithopter can be found in [21].…”
Section: A Force and Moment Identification Resultsmentioning
confidence: 99%
“…Thus, to prevent p, q, r from feeding wrong information into the force and moments equations, new attitude angles were devised. This methodology is explained in [21].…”
Section: Applicability Aspectsmentioning
confidence: 99%
“…The procedure started with a series of flight tests at specified trim conditions [32], [33]. Afterwards, Flight Path Reconstruction techniques were applied that, together with a set of assumptions (Section II-B3), led to the proposed dynamics model and consequent calculation of the acting forces and moments.…”
Section: B Free Flight Testsmentioning
confidence: 99%
“…More recently, Caetano et al [31], [32] reconstructed the forces and moments that acted on a tailed ornithopter (the DelFly II) in a series of more than 200 flight tests that covered the FWMAV's full flight envelope. The tests were performed in a motion cueing flight chamber in which several identification maneuvers were performed with a flying DelFly II.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, when flight data is obtainable, an attractive modelling option, in alternative to often complex and computationally expensive theoretical or numerical models, is system identification. Previous system identification efforts [19,20,21,22,23,24,25] showed that a data-driven approach can yield realistic but simple models, as well as new insight, for a novel and complex type of vehicle, that is not known in great depth. However relatively limited work has been done in this field so far, largely due to the difficulty of obtaining suitable data.…”
Section: Introductionmentioning
confidence: 99%